2016
DOI: 10.3892/br.2016.718
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between periodontitis and liver diseases

Abstract: Abstract.Periodontitis is an oral disease that is highly prevalent worldwide, with a prevalence of 30-50% of the population in developed countries, but only ~10% present with severe forms. It is also estimated that periodontitis results in worldwide productivity losses amounting to ~54 billion USD yearly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 148 publications
(128 reference statements)
0
61
0
3
Order By: Relevance
“…In the current literature, the association between periodontal disease and liver injury has been lately reported . Several papers have demonstrated that the presence of hepatic inflammation after ligature induced periodontitis around molars .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current literature, the association between periodontal disease and liver injury has been lately reported . Several papers have demonstrated that the presence of hepatic inflammation after ligature induced periodontitis around molars .…”
Section: Discussionmentioning
confidence: 99%
“…The link between periodontal disease and liver injury has been mentioned in the review of Han et al . Periodontal structures produce inflammatory cytokines and periodontal bacteria, which are translocated via bloodstream to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have found associations between periodontitis and systemic disease, including cardiovascular disease, kidney disease, obesity and adverse pregnancy outcomes . Emerging evidence also suggests a link to liver disease …”
Section: Introductionmentioning
confidence: 99%
“…It is routine clinical practice to treat periodontitis prior to liver transplant in order to eliminate all potential infectious foci and reduce the risk of postsurgical complications (76). In addition to potentially affecting transplant outcomes, periodontitis is associated clinically with liver diseases such as precirrhotic NAFLD, cirrhosis, and hepatocellular carcinoma (77). While the studies are still limited and a link between periodontal and liver diseases is not as well established as associations between periodontitis and other systemic conditions, such as diabetes and cardiovascular disease (78), it is likely that similar factors related to the oral microbiota and inflammation connect oral and liver disease, as well.…”
Section: Ahluwalia Et Al 2016 (56)mentioning
confidence: 99%